THE IMPACT OF CORPORATE GOVERNANCE, DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY, AND PROFITABILITY ON TAX AVOIDANCE - Sudiarto, Edi; Nurfaiza, Jihan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2022)
The purpose of this research is to analysis the impact of corporate governance (institutional ownership, independent commissioners, audit committees), corporate social responsibility disclosure, and profitability on tax avoidance. This study uses method known as causality research. This study included 16 manufacturing businesses from the basic and chemical industries that were listed on the Indonesia Stock Exchange between 2016 and 2019. The purposive sampling approach is used to pick the samples. Multiple linear regression analysis was employed as the analytical method in this study. Institutional ownership, independent commissioners, audit committees, and profitability have no influence on tax avoidance, according to the findings of this study. Meanwhile, corporate social responsibility disclosure has a large positive impact on tax avoidance.